Pengaruh Religiusitas, Status Sosial Ekonomi dan Love Of Money Pada Persepsi Etis Mahasiswa Akuntansi dari Perspektif Gender (Studi pada Mahasiswa Akuntansi Universitas Islam Malang Angkatan 2020) - Ainiyah, Zahrotul; Sudaryanti, Dwiyani; Mahsuni, Abdul Wahid (Universitas Islam Malang, 2024)
This research aims to examine the influence of religiosity, socio-economic status and love of money on accounting students' ethical perceptions from a gender perspective. The research population was all accounting students at the University of Islamic Malang class of 2020 who were still active, totaling 144 students. The research sample consisted of 120 respondents using the Slovin formula. The research uses multiple analysis techniques. data was collected using the questionnaire method. it can be concluded that religiosity has no effect on accounting students' ethical perceptions from a gender perspective. Socioeconomic status has no effect on accounting students' ethical perceptions from a gender perspective. love of money has a positive influence on accounting students' ethical perceptions from a gender perspective.Keyword: Religiosity, socio-economic status, love of money, ethical perceptions, accounting students, gender